(untitled) (Impact: Journal of Transformation, 2020)
Strategic implementation has remained a big challenge for leaders in nonprofit organisations. It is easy to draft a strategic document without practical steps to implement the plan. The role of leaders is very crucial in planning how the organisation will succeed through critical engagement with resource personnel in developing a meaningful strategic document that will guide them on a daily basis to accomplish organisational goals. The purpose of this study is to find out the factors that hinder the implementation of the strategic plan among leaders at Karen Community Church Nairobi Kenya. This study identified five hindrances to the implementation of strategic plans. These include having a bad strategic plan, lack of commitment to the strategic plan, lack of communication of strategic objectives, lack of motivation of workers, and a lack of financial mobilisation. Based on this, the bridge gap model was proposed to help local church leaders overcome the challenges faced between what is planned and its implementation. The approach used is a quantitative method using a descriptive survey design to describe the phenomenon under study. Additionally, the regression model was used to test the strength of the relationship between variables. Conversely, a review of the literature was carried out to understand the concept of strategic planning and implementation. Strategic implementation has remained a big challenge for leaders in nonprofit organisations. It is easy to draft a strategic document without practical steps to implement the plan. The role of leaders is very crucial in planning how the organisation will succeed through critical engagement with resource personnel in developing a meaningful strategic document that will guide them on a daily basis to accomplish organisational goals. The purpose of this study is to find out the factors that hinder the implementation of the strategic plan among leaders at Karen Community Church Nairobi Kenya. This study identified five hindrances to the implementation of strategic plans. These include having a bad strategic plan, lack of commitment to the strategic plan, lack of communication of strategic objectives, lack of motivation of workers, and a lack of financial mobilisation. Based on this, the bridge gap model was proposed to help local church leaders overcome the challenges faced between what is planned and its implementation. The approach used is a quantitative method using a descriptive survey design to describe the phenomenon under study. Additionally, the regression model was used to test the strength of the relationship between variables. Conversely, a review of the literature was carried out to understand the concept of strategic planning and implementation.